Triploid Hybrid Vigor in Above-Ground Growth and Methane Fermentation Efficiency of Energy Willow - Dudits, Dénes; Cseri, András; Török, Katalin; Sass, László; Zombori, Zoltán; Ferenc, Györgyi; Poór, Péter; Borbély, Péter; Czékus, Zalán; Vankova, Radomira; Dobrev, Petre; Szántó, Judit; et al. (Frontiers in Plant Science, 2022)
Hybrid vigor and polyploidy are genetic events widely utilized to increase the productivity of crops. Given that bioenergy usage needs to be expanded, we investigated triploid hybrid vigor in terms of the biology of biomass-related willow traits and their relevance to the control of biomethane production. To produce triploid hybrid genotypes, we crossed two female diploid Swedish cultivars (Inger, Tordis) with two male autotetraploid willow (Salix viminalis) variants (PP-E7, PP-E15). Field studies at two locations and in two successive years recorded considerable midparent heterosis (MPH%) in early shoot length that ranged between 11.14 and 68.85% and in the growth rate between 34.12 and 97.18%. The three triploid hybrids (THs) developed larger leaves than their parental cultivars, and the MPH% for their CO2 assimilation rate varied between 0.84 and 25.30%. The impact of hybrid vigor on the concentrations of plant hormones in these TH genotypes reflected essentially different hormonal statuses that depended preferentially on maternal parents. Hybrid vigor was evinced by an elevated concentration of jasmonic acid in shoot meristems of all the three THs (MPH:29.73; 67.08; 91.91%). Heterosis in auxin-type hormones, such as indole-3-acetic acid (MPH:207.49%), phenylacetic acid (MPH:223.51%), and salicylic acid (MPH:27.72%) and benzoic acid (MPH:85.75%), was detectable in the shoots of TH21/2 plants. These hormones also accumulated in their maternal Inger plants. Heterosis in cytokinin-type hormones characterized the shoots of TH3/12 and TH17/17 genotypes having Tordis as their maternal parent. Unexpectedly, we detected abscisic acid as a positive factor in the growth of TH17/17 plants with negative MPH percentages in stomatal conductance and a lower CO2 assimilation rate. During anaerobic digestion, wood raw materials from the triploid willow hybrids that provided positive MPH% in biomethane yield (6.38 and 27.87%) showed negative MPH in their acid detergent lignin contents (from –8.01 to –14.36%). Altogether, these insights into controlling factors of above-ground growth parameters of willow genotypes support the utilization of triploid hybrid vigor in willow breeding to expand the cultivation of short rotation energy trees for renewable energy production.